Numerical simulation of thermal insulation and longevity performance in new lightweight ladle. (18th June 2020) - Sun, Ying; Tian, Jinrong; Jiang, Du; Tao, Bo; Liu, Ying; Yun, Juntong; Chen, Disi
Summary: For meeting the comprehensive requirements of "super insulation, " "lightweight, " and "longevity" of the contemporary ladle, this article designs a new kind of lightweight ladle with heat preservation and longevity performance, and based on steady‐state analysis method and numerical simulation technology, the comparison of temperature distribution between new lightweight and traditional ladle under typical operating modes is made and analyzed. The simulation results of temperature field prove that the performance of heat preservation in new kind of lightweight ladle has been improved obviously from the two aspects of ladle shell temperature and molten steel file rate. At the same time, the simulation results of stress field indicate that the stress of designed lightweight ladle reduced and distributed more evenly, which is conducive to prolonging the work time in‐service of the ladle. Finally, based on the field test, the simulation is proved to be effective, and the designed ladle structure achieves the expected purpose.